Javanese Language Attitude towards Speech Levels of Vernacular in Kelurahan Bandar Selamat Medan - Farida Romaito Pohan; Lince Sihombing (Universitas Negeri Medan, 2016)
This study explains Javanese Language Attitude towards Speech Levels of Vernacular in Kelurahan Bandar Selamat Medan. The objective of this study are (1) to describe the kinds of Javanese speech levels use in Kelurahan Bandar Selamat Medan (2) to investigate the characteristics of Javanese language when they use the dominant speech level (3) to explain the attitude toward their vernacular. The method of this study was qualitative research. The subjects were 30 Javanese speakers’ who live in Kelurahan Bandar Selamat Medan taken by purposive random sampling. Questionnaire was used to collect the data to answer the Javanese speakers attitude in using their vernacular. While the interview was used to get the real data of them by transcribing their utterances during communication by using Javanese language. The data were analyzed by using interactive model by Miles and Huberman. This research result: (1) There are two kinds of Javanese speech levels in Kelurahan Bandar Selamat Medan, they are Madya and Ngoko, (2) The characteristic of language in Kelurahan Bandar Selamat Medan show that they have high loyalty to their vernacular, (3) Javanese speakers in Kelurahan Bandar Selamat Medan have positive attitude toward their vernacular. Keywords: Language attitude, vernacular, speech levels, Javanese language